Formation of the Soviet education system among the indigenous peoples of Southern Siberia in the 1920s - L. N. Aksenova; L. V. Sokolskaya; A. S. Valentonis; I. V. Shcherbinina (Obrazovanie i Nauka)
Introduction. In the era of the formation of the world educational space, historical and pedagogical studies of regional education systems acquire special relevance. Many states, while modernising their national education systems, turn to the experience of past generations in order to understand how socio-economic changes taking place around the world and in Russia can affect the education system of a particular region. The twenties of the last century in Russia is a time of searching for new types of schools, opportunities for educating and teaching the younger generation in the spirit of the new (Soviet) ideology. The peoples of South Siberia (Altai, Shors, Kumandins, Chelkans, Teleuts, Tubalars, Telengits), united in the administrative-territorial framework of the Oirot Autonomous Region and the Gorno-Shor National Region, despite the difficulties, made a significant progress in the development of school education, including the number of the national school.The aim of the present article was to study the peculiarities of the process of formation and development of the Soviet education system among the indigenous peoples of Southern Siberia in the 1920s.Methodology and research methods. The research is based on the analysed and generalised content of archival documents, scientific sources on the history of the formation of the peoples of Southern Siberia in the context of the system-historical approach. The authors of the article studied 35 documents from the funds of the Committee for Archives of the Altai Republic and the Center for the Storage of Archives of the Altai Territory. The archival documents introduced into scientific circulation made it possible to consider the process of increasing the number of national schools, providing students with textbooks in their native language, the process of training teachers from the indigenous population, taking into account the national and cultural characteristics of the region.Results and scientific novelty. Based on the study of archival materials, the authors of the article rethink the activities of the Soviet authorities to restore and create the school network of education, its development and preparation for the introduction of universal primary education among the peoples of Southern Siberia. The issue of creating a national education system in the 1920s is closely connected with the process of indigenisation, as part of the national policy of the Soviet state and with the process of transferring the local population to settled life. By the beginning of the 1930s, a network of school institutions was created in the region, which increased the percentage of literate adolescents and subsequently enrolled in primary education all children of school age. Addressing national inequalities through the development of the education system and the eradication of illiteracy in the multinational region is of undeniable interest to educational historians and teachers.Practical significance. Today, the interest of researchers in regional history has increased all over the world; therefore, the current article will be useful to readers, as the analysis of new archival documents helps to fill the gaps in the scientific literature on the establishment of the Soviet school among the indigenous peoples of southern Siberia in the 1920s. The materials of the article can be used by teachers to design the courses on the history of education in Russia and the historical study of local lore. Moreover, the presented materials can be applied in the course of the development of a modern regional educational policy.